Rationing training loads for free style wrestler in the light of some functional responses - Darwish, T. M. (International Journal of Sports Science and Arts, 2019)
The aim of the study is to identify the functional responses with changing intensity loads for free style junior wrestler, through the identification of the relation between theses functional variables and intensity load the sample of the study consist of (16) junior player from sports school the researcher have used the descriptive method and the most important result of this study is to recognize the contribution rate of some functional variables responses with changing intensity of training loads, and equations have been reached to predict each intensity load of changing intensity.